2022
DOI: 10.1080/21655979.2021.2018979
|View full text |Cite
|
Sign up to set email alerts
|

GATA binding protein 5-mediated transcriptional activation of transmembrane protein 100 suppresses cell proliferation, migration and epithelial-to-mesenchymal transition in prostate cancer DU145 cells

Abstract: It has been reported that transmembrane protein 100 (TMEM100) acts as a tumor regulator in several types of cancers. However, whether the expression of TMEM100 is associated with the development and prognosis of prostate cancer (PCa) remains elusive. Therefore, the present study aimed to uncover the role of GATA binding protein 5 (GATA5)-mediated activation of TMEM100 in the proliferation, migration and epithelial-to-mesenchymal transition (EMT) of PCa cells. The expressions of TMEM100 and GATA5 in PCa patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 42 publications
(41 reference statements)
0
8
0
Order By: Relevance
“…Furthermore, TMEM100 was markedly downregulated in pancreatic cancer (PCa) tissues. Overexpression of TMEM100 attenuates the proliferation, migration, invasion and EMT in DU145 cells, a PCa cell line 34 . Similarly, TMEM100 was shown to decrease in the prostate cancer patients, and low TMEM100 expression was associated with advanced tumor stage and metastasis.…”
Section: Role Of Tmem100mentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, TMEM100 was markedly downregulated in pancreatic cancer (PCa) tissues. Overexpression of TMEM100 attenuates the proliferation, migration, invasion and EMT in DU145 cells, a PCa cell line 34 . Similarly, TMEM100 was shown to decrease in the prostate cancer patients, and low TMEM100 expression was associated with advanced tumor stage and metastasis.…”
Section: Role Of Tmem100mentioning
confidence: 99%
“…However, we did not observe significantly change of TMEM100 expression in the lung of hypoxia treated mice. TMEM100 expression is downregulated in multiple cancer tissue and cell lines including lung adenocarcinoma (LUAD) and lung squamous cell carcinoma (LUSC), colorectal cancer, gastric cancer, and PCa 28,31,34,50,51 . Liu et al demonstrated that GATA binding 5 (GATA5) , a transcription factor of GATA protein family 52 , binds to TMEM100 promoter and transcriptionally activates TMEM100 and suppresses PCa progression 34 .…”
Section: Regulation Of Tmem100 Expressionmentioning
confidence: 99%
See 1 more Smart Citation
“…This suggests that TMEM100 is most likely to be involved in processes such as malignant tumor metastasis and the induction of microangiogenesis. TMEM100 exhibited a clear inhibition of metastasis and proliferation in lung cancer, prostate cancer (PC), hepatocellular carcinoma (HCC) and gastric cancer (GC), and is correlated with the prognostic outcomes of above malignancies (5)(6)(7)(8)(9)(10)(11). In lung adenocarcinoma, miR-421 could be sponged by circ_0000567 and directly target TMEM100 mRNA, then regulated the migration and invasion (5).…”
Section: Introductionmentioning
confidence: 99%
“…And Histone deacetylase 6 (HDAC6) acted as a metastasis supporter induced the Wnt/β-catenin signaling pathway by suppressing TMEM100 expression in non-small cell lung cancer (NSCLC) ( 6 ). In PC, GATA binding protein 5-mediated transcriptional activation of TMEM100 suppresses cell proliferation, migration and epithelial-to-mesenchymal transition ( 7 ). Elevated TMEM100 level inhibits pulmonary metastasis of GC cells and enhances xenograft tumor sensitivity to 5-FU therapy ( 9 ).…”
Section: Introductionmentioning
confidence: 99%